Manuel Martínez Curbelo, a brilliant university student and universal anesthesiologist - Carlos Antonio Vilaplana Santaló (Revista Cubana de Anestesiología y Reanimación, 2017)
Introduction: On January 13, 2017, the 70th anniversary was celebrated for the first administration of the continuous epidural anesthesia in Havana, Cuba, and the world, by the most universal of Cuban anesthesiologists in the 20th century, doctor Manuel Martínez Curbelo. The objective of this work was to make an update about the life and work of Dr. Manuel Martínez Curbelo. This brilliant university student and tireless researcher became the Cuban anesthesiologist with more contributions to worldwide anesthesiology in the last century. Cuban anesthesiologists must transmit to the new generations of Cuban anesthesiologists the knowledge about the life and work of this physician as a role model. His constant dedication to the specialty is a worthy example to be imitated by future generations of Cuban anesthesiologists.